Estimating returns to education when the IV sample is selective - Le Wang (Institute for the Study of Labor (IZA), 2012)
The literature estimating returns to education has often utilized spousal education and parental education as instrument variables (IV). However, due to usual survey designs, both IVs are available only for the individuals whose spouse or parents are present in the same household. The IV estimates based on these selective sub-samples may be inconsistent, even when the IVs satisfy the standard assumptions. In this paper, we examine the empirical relevance of this issue in the Chinese context. To our surprise, unlike the selection issue in other situations, this kind of selection does not appear particularly worrisome, suggesting that the previous IV results are robust. In particular, using China Household Income Project 1995 and 2002, we find that correcting for this potential issue has only a modest impact on the magnitude of the standard IV estimates using parental education as an IV, but a negligible impact on those using spousal education. Using the specification tests proposed, we find that these impacts are generally not statistically significant. These results are further confirmed by our analysis using U.S. data. We believe that these results are of use to both policymakers and practitioners.
Keywords: J24; I21; C14; C31; P52; 330; returns to education; sample selection; instrument variable estimation; Chinese labor market; Bildungsertrag; Statistisches Auswahlverfahren; Instrumentalvariablen-Schätzmethode; Arbeitsmarkt; Schätzung; China